Radiation shielding of electron accelerator LIAM-2: calculation and geometry - Mazilov, A.V.; Razsukovannyj, B.N.; Degtyar, J.A.; Vinokurov, V.A. (Вопросы атомной науки и техники, 2006)
In the present paper the calculation is carried out and the geometry of radiation shielding construction for a linear induction electron accelerator LIAМ-2 with the energy of 2 MeV and current in a pulse 3∙10³ A developed at the NSC KIPT is offered. It is shown that despite high accelerated electron current in the accelerator using a ferromagnetic tape, by a virtue of practical absence of beam dispersion in a transportation path, and specificity of X-ray bremsstrahlung topography, it is possible to realize, the effective radiation shielding of the personnel of categories "A" and "B" serving the accelerator with the aid of, for instance, lead. Выполнен расчет и предложена геометрия построения радиационной защиты разработанного в ННЦ ХФТИ линейного индукционного ускорителя электронов ЛИУМ-2 с энергией 2 МэВ и током в импульсе 3∙10³ A. Показано, что, несмотря на большой ускоряемый ток электронов в ускорителе, использующем ферромагнитную ленту, в силу практического отсутствия рассеяния пучка в тракте транспортировки, специфики топографии тормозного рентгеновского излучения, можно осуществить эффективную радиационную защиту обслуживающего ускоритель персонала категорий «А» и «Б», используя, например, свинец. Виконано розрахунок та запропонована геометрія побудови радіаційного захисту розробленого в ННЦ ХФТІ лінійного індукційного прискорювача електронів ЛІПМ-2 з енергією 2 МеВ і струмом в імпульсі 3∙10³ А. Показано, що, незважаючи на великий струм електронів у прискорювачі, який використовує феромагнітну стрічку, в силу практичної відсутності розсіювання пучка в тракті транспортування, специфіки топографії гальмового рентгенівського випромінювання, можна здійснити ефективний радіаційний захист персоналу категорій "А" і "Б", що обслуговує прискорювач, використовуючи, наприклад, свинець.